Stable Oxidative Cytosine Modifications Accumulate in Cardiac Mesenchymal Cells From Type2 Diabetes Patients: Rescue by α-Ketoglutarate and TET-TDG Functional Reactivation. Issue 1 (5th January 2018) - Spallotta, Francesco; Cencioni, Chiara; Atlante, Sandra; Garella, Davide; Cocco, Mattia; Mori, Mattia; Mastrocola, Raffaella; Kuenne, Carsten; Guenther, Stefan; Nanni, Simona; Azzimato, Valerio; Zukunft, Sven; et al.
Abstract : Rationale: : Human cardiac mesenchymal cells (CMSCs) are a therapeutically relevant primary cell population. Diabetes mellitus compromises CMSC function as consequence of metabolic alterations and incorporation of stable epigenetic changes. Objective: : To investigate the role of α-ketoglutarate (αKG) in the epimetabolic control of DNA demethylation in CMSCs. Methods and Results: : Quantitative global analysis, methylated and hydroxymethylated DNA sequencing, and gene-specific GC methylation detection revealed an accumulation of 5-methylcytosine, 5-hydroxymethylcytosine, and 5-formylcytosine in the genomic DNA of human CMSCs isolated from diabetic donors. Whole heart genomic DNA analysis revealed iterative oxidative cytosine modification accumulation in mice exposed to high-fat diet (HFD), injected with streptozotocin, or both in combination (streptozotocin/HFD). In this context, untargeted and targeted metabolomics indicated an intracellular reduction of αKG synthesis in diabetic CMSCs and in the whole heart of HFD mice. This observation was paralleled by a compromised TDG (thymine DNA glycosylase) and TET1 (ten–eleven translocation protein 1) association and function with TET1 relocating out of the nucleus. Molecular dynamics and mutational analyses showed that αKG binds TDG on Arg275 providing an enzymatic allosteric activation. As a consequence, the enzyme significantly increased its capacity to remove G/T nucleotide mismatches or 5-formylcytosine. Accordingly, an exogenous source of αKG restored the DNA demethylation cycle by promoting TDG function, TET1 nuclear localization, and TET/TDG association. TDG inactivation by CRISPR/Cas9 knockout or TET/TDG siRNA knockdown induced 5-formylcytosine accumulation, thus partially mimicking the diabetic epigenetic landscape in cells of nondiabetic origin. The novel compound (S)-2-[(2, 6-dichlorobenzoyl)amino]succinic acid (AA6), identified as an inhibitor of αKG dehydrogenase, increased the αKG level in diabetic CMSCs and in the heart of HFD and streptozotocin mice eliciting, in HFD, DNA demethylation, glucose uptake, and insulin response. Conclusions: : Restoring the epimetabolic control of DNA demethylation cycle promises beneficial effects on cells compromised by environmental metabolic changes. Abstract : Supplemental Digital Content is available in the text.